Social Inclusion in Jamasan Pusaka as a Strategy to Preserve Cultural Heritage: A Study in Kalibening, Dawuhan, Banyumas - Hidayat, Arif; Fauji, Sidik; Adzkiya Zayyan , Mauiza (Indonesian Academy of Social and Religious Research (IASRR), 2024)
This research explores social inclusion in the Jamasan Pusaka ceremony in Kalibening, Dawuhan, Banyumas as a strategy to preserve cultural heritage. The study finds that the practice of inclusion involves the community, the village government, and the Banyumas Regency Culture and Tourism Office. The form of Islam practised in Dawuhan Village accommodates the culture and customs inherited by the ancestors. This can be seen in the 2019 Jamasan Pusaka ceremony, which included the recitation of shalawat and religious lectures, unlike in previous years. The involvement of the village government is shown through the granting of permits. This support ensures the smooth running of the event through official authorization and assistance. The relationship between the Jamasan Pusaka ceremony and the Department of Culture and Tourism is evident from the department's participation in giving a speech before the ceremony began, which showed their support and motivated the Kalibening community to organize the event. The efforts made by the Kalibening community to preserve this cultural heritage include teaching how to perform the Jamasan Pusaka ceremony and taking the benefits of the ceremony. They are trained to appreciate Jamasan Pusaka by understanding every step of the tradition.